Molybdate‐Modified NiOOH for Efficient Methanol‐Assisted Seawater Electrolysis - Zhen Li; Youbin Zheng; Wenhan Zu; Liang Dong; Lawrence Yoon Suk Lee (Advanced Science)
Abstract Seawater electrolysis holds great promise for sustainable, green hydrogen production but faces challenges of high overpotentials and competing chlorine evolution reaction (CER). Replacing the oxygen evolution reaction with the methanol oxidation reaction (MOR) presents a compelling alternative due to its lower anodic potential which mitigates the risk of CER. While NiOOH is known for its MOR activity, its performance is limited by sluggish non‐electrochemical kinetics and Cl‐induced degradation. Herein, a MoO42−‐modified NiOOH electrocatalyst is reported that significantly enhances MOR‐assisted seawater splitting efficiency. In situ leached MoO42− from the heterojunction optimizes methanol adsorption and facilitates proton migration, thereby accelerating the non‐electrochemical steps in MOR. Additionally, the adsorbed MoO42− effectively repels Cl−, protecting the electrodes from Cl−‐induced corrosion. The MOR‐assisted electrolyzer using NiMo||Ni(OH)2/NiMoO₄ requires only 1.312 V to achieve 10 mA cm−2, substantially lower than conventional alkaline seawater electrolysis (1.576 V). Furthermore, it demonstrates remarkable stability, sustaining high current densities (up to 1.0 A cm−2) for over 130 h. This work presents a promising strategy for designing high‐performance electrocatalysts for efficient and sustainable green hydrogen production from seawater.